Analysis on the Effectiveness of the Wira-Wiri Suroboyo Feeder in Increasing Urban Mobility Using Participant Observation Method - Andita Wibyasti Sari Putri; Putri Dwitasari; Didit Prasetyo; Ifanny Nur Baiti (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DRPM), ITS, 2025)
The Feeder Wira-Wiri Suroboyo is a transportation service specifically designed to enhance connectivity and efficiency within Surabaya's public transportation network, particularly by serving areas that are not accessible by regular buses. Despite being a well-managed public transportation service overseen by the city government, this form of transportation has not successfully encouraged widespread participation from the Surabaya community in its utilization.The purpose of this study was to identify operational problems in the Feeder Wira-Wiri Suroboyo using the participant observation method. Observations were conducted on different days and times to evaluate performance and identify strengths and weaknesses in feeder operations. The participant observation method involved researchers who actively used the service to gain direct experience and accurate data. The findings showed that although the feeder operated effectively, especially during peak hours, and provided adequate basic facilities, there were several areas that needed improvement. The primary problems identified include extended waiting times, the absence of an audio information system or notification system, and inaccuracies in application-based tracking. In order to improve operational effectiveness, recommended improvements are in waiting times, development of an audio notification system, and accuracy of application tracking. This study provides a reference for the Surabaya City Government to further improve the Feeder Wira-Wiri Suroboyo service so that it can be an alternative means of transportation to reduce congestion in the city of Surabaya.